Modularizing application and database evolution – an aspect‐oriented framework for orthogonal persistence. (8th June 2016) - Pereira, Rui Humberto R.; García Perez‐Schofield, J. Baltasar; Ortin, Francisco
Summary: In the maintenance of software applications, database evolution is one common difficulty. In object‐oriented databases, this process comprises schema evolution and instance adaptation. Both tasks usually require significant effort from programmers and database administrators. In this paper, we propose orthogonal persistence and aspect‐oriented programming to support semi‐transparent database evolution. A default mechanism for instance evolution is defined, but the user may provide modularized solutions using the aspect‐oriented paradigm. We present our framework AOF4OOP to test the feasibility of our proposed approach. This prototype allows programmes to transparently access data in other versions of the database schema. We evaluate our framework, comparing it to related approaches using two real applications and measuring the improvement of the productivity of the programmer. Copyright © 2016 John Wiley & Sons, Ltd.